Effects of selective serotonin-reuptake inhibitors (SSRIs) in JEG-3 and HIPEC cell models of the extravillous trophoblast. (December 2018) - Clabault, Hélène; Cohen, Marie; Vaillancourt, Cathy; Sanderson, J. Thomas
Abstract: Introduction: Between 2 and 10% of pregnant women are treated with selective serotonin-reuptake inhibitors (SSRIs) for depression. The extravillous trophoblasts (evTBs), which migrate and invade maternal tissues, are crucial for embryo implantation and remodeling of maternal spiral arteries. Poor migration/invasion of evTBs can cause serious pregnancy complications, yet the effects of SSRIs on these processes has never been studied. To determine the effects of five SSRIs (fluoxetine, norfluoxetine, citalopram, sertraline and venlafaxine) on migration/invasion, we used JEG-3 and HIPEC cells as evTB models. Methods: Cells were treated with increasing concentrations (0.03–10 μM) of SSRIs. Cell proliferation was monitored using an impedance-based system and cell cycle by flow cytometry. Migration was determined using a scratch test, and metalloproteinase (MMP) activities, by zymography. Invasion markers were determined by RT-qPCR. Results: Fluoxetine and sertraline (10 μM) significantly decreased cell proliferation by 94% and by 100%, respectively, in JEG-3 cells, and by 58.6% and 100%, respectively, in HIPEC cells. Norfluoxetine increased MMP-9 activity in JEG-3 cells by 2.0% at 0.03 μM and by 43.9% at 3 μM, but decreased MMP-9 activity in HIPEC cells by 63.7% at 3 μM. Sertraline at 0.03 μM increased mRNA level of TIMP-1 in JEG-3 cells by 36% and that of ADAM- 10 by 85% and 115% at 0.3 and 3 μM, respectively. In HIPEC cells, venlafaxine at 0.03 and 0.3 μM, increased ADAM- 10 mRNA levels by 156% and 167%, respectively. Discussion: This study shows that SSRIs may affect evTBs homeostasis at therapeutic levels and provides guidance for future research. Highlights: SSRIs disrupt extravillous trophoblast-like cell homeostasis. Fluoxetine and sertraline reduce JEG-3 and HIPEC cell proliferation. Norfluoxetine increases MMP-9 activity in JEG-3 and decreases it in HIPEC cells. Venlafaxine increases HIPEC cell migration and ADAM10 expression. Fluoxetine decreases, whereas NF increases JEG-3 cell migration.